Culinary medicine in medical education: a pilot study targeting cancer risk reduction strategies through culinary and lifestyle medicine education - Stephanie R. Harris; Elaine Borawski; Ryanne Lachman; Lindsay Malone; Jessica DePalma; Hope Barkoukis (Frontiers in Nutrition)
IntroductionCulinary Medicine (CM) is an avenue for interdisciplinary nutrition education intervention utilizing the expertise of dietitians, physicians, and other health care professionals (HCP). Despite the positive impacts that CM interventions can have on health, physician CM knowledge is lacking due in part to inadequate nutrition education in medical school curriculum. CM as a nutrition education modality promotes health and disease management for patients and providers, so it is critical to increase competency in CM. This pilot study evaluated the impact of a cancer prevention specific CM curriculum on medical students’ (i) cancer risk reduction (CRR) knowledge, (ii) CRR assessment/counseling attitudes and self-efficacy in clinical care, and (iii) personal health behaviors and cooking skills.MethodsThirty-one 2nd year medical students (CALM students) participated in seven, 3-hour CRR focused CM education sessions and were compared to 55 non-enrolled students (control group). Education sessions incorporated a lecture, learning activity, and cooking experience focused on topics including dietary patterns, gut health, inflammation, metabolic health, hormone balance, environmental exposures, and prevention in practice/at home. A 46-item online pre-test (09/23) and post-test (03/24) survey assessed standardized measures of general nutrition/cancer knowledge, attitudes/beliefs, perceived control and self-efficacy around CRR diet/ lifestyle modifications; and intentions of integrating CRR strategies in practice.Results78 students (91%) completed both surveys and the findings indicate that CALM students showed significant improvement over their peers in knowledge scores (β = 0.265, t = 2.14, p < 0.05), attitudes toward nutrition in the clinical setting (β = 0.203, t = 2.00, p < 0.05) and confidence in integrating CRR strategies in patient care (β = 0.401, t = 4.05, p < 0.001). Most significant changes occurred in confidence of being able to make a CRR plan and follow through with patients on the plan (p < 0.001).DiscussionThis pilot study is among the first to incorporate and evaluate CRR-specific CM competencies in medical education. Given that the lifetime risk for developing cancer is high for Americans (~40%), education and implementation of CRR strategies among patients and providers must be emphasized. If research continues to demonstrate curriculum success in future cohorts, it is an innovative approach to teaching nutrition and CM competencies to HCP that is applicable to numerous disease states.